Perceived Constraints and Challenges in the Compliance and Implementation of OBE Syllabus of West Visayas State University- Extension Campus at Himamaylan City - Mary Lord Casiano; Zoilo Andrada, Jr (Philippine Association of Institutions for Research, Inc., 2019)
Teachers in the 21st century are encouraged to upgrade their teaching from a teacher-centered approach to a student-centered approach to address the demands of globalization. This qualitative research aimed to discuss the perceived constraints and challenges in the compliance and implementation of the Outcomes-Based Education syllabus by the teachers who are handling Social Sciences courses in West Visayas State University- Extension Campus at Himamaylan City. Data were obtained with the use of the Triangulation Method in the form of a Survey questionnaire, Focus Group Discussion, and Document Analysis. Results showed that teachers' understanding from the training and seminar workshop attended is not enough because their understanding is only focused on the format to be used and not on the application inside the classroom. In terms of the submission of the OBE syllabus, there is monitoring, but it lacks the feedbacks in monitoring the content. Teachers are encouraged to attend training because training implies application. The school shall organize a monitoring mechanism in the implementation of the OBE syllabus inside the classroom. For monitoring mechanisms, the school may tap experts to check the contents of the submitted OBE course syllabi by the teachers. To ensure that the syllabus is being implemented inside the classroom, close monitoring through class observation by the school heads may be implemented at least twice per semester.